Boiling : Research and Advances - Koizumi, Yasuo, editor 635907; Shōji, Masahiro, editor 649470; Monde, Masanori, editor 649471; Takata, Yasuyuki, editor 649472; Nagai, Niro, editor 649473; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2017)
Boiling: Research and Advances presents the latest developments and improvements in the technologies, instrumentation, and equipment surrounding boiling. Presented by the Japan Society of Mechanical Engineers, the book takes a holistic approach, first providing principles, and then numerous practical applications that consider size scales.